PLL-less Robust DeadBeat-response Direct Power Control of Grid-Tie Three-Phase Inverters - J.R. Fischer (Revista Iberoamericana de Automática e Informática Industrial RIAI, 2015)
A new type of PLL-less Direct Power Control with robust implementation and deadbeat response is presented for grid-tie inverters. In this work a novel positive sequence detector is also implemented which ensures the elimination of perturbation at the output current due to harmonics content. The control algorithm has an intrinsic synchronization scheme which avoids an additional three-phase PLL. This maximizes the response time and power tracking achieving precise power step reference change in less than 200 μs. The results obtained are shown with both simulations and experiential results in a 15kW three-phase inverter that verifies the performance of the proposed controller, yielding low-harmonics output currents even in abnormal operating situations.